2016
DOI: 10.1177/2047487316670256
|View full text |Cite
|
Sign up to set email alerts
|

eHealth in cardiovascular medicine: A clinical update

Abstract: Demographic changes, progress in medicine technology and regional problems in providing healthcare to low density populations are posing great challenges to our healthcare systems. Rapid progress in computer sciences and information technologies have a great impact on the way healthcare will be delivered in the near future. This article describes opportunities and challenges of eHealth and telemedicine in the framework of our health systems and, in particular, in the context of today's cardiology services. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 62 publications
(93 reference statements)
1
64
0
2
Order By: Relevance
“…She quickly identified a sample of highly-cited review articles covering both quantitative and qualitative research [5, 7, 17, 21, 38, 52, 65, 6870]. She used citation tracking in Google Scholar to identify subsequent articles that had cited these seminal sources [71].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…She quickly identified a sample of highly-cited review articles covering both quantitative and qualitative research [5, 7, 17, 21, 38, 52, 65, 6870]. She used citation tracking in Google Scholar to identify subsequent articles that had cited these seminal sources [71].…”
Section: Methodsmentioning
confidence: 99%
“…The use of telehealth technology in heart failure management remains controversial, with some clinicians and policymakers strongly enthusiastic [1–4] and others unconvinced or opposed [57]. Despite dozens of randomised controlled trials (including several megatrials [813]), over 20 systematic reviews and meta-analyses of clinical trials [14–33] and (at last count) 7 systematic reviews of systematic reviews [6, 3439], as well as studies of cost-effectiveness [21, 4043], the patient experience [18, 24, 44–47] and service organisation [32, 48–51], there is limited agreement on which outcomes matter; the extent to which telehealth adds benefit over usual care; how best (if at all) to change service models to support telehealth; and whether and in what circumstances telehealth is cost-effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of modern eHealth applications to monitor BP at home intensifies patient involvement and increases motivation for healthy lifestyle adherence and better intake of prescribed medication. 11 This needs to be further explored in this potentially very suitable patient group.…”
Section: Severity Of Hpd Is Leadingmentioning
confidence: 99%
“…18 The arrival on the market of PA sensors (pedometers, accelerometers, global positioning system) has facilitated the continuous out-of-hospital measurement of the amount of PA of both healthy subjects and patients. 19 However, it is here demonstrated that wearable sensors are not accurate enough and underestimate the actual energy expenditure values in post-stroke patients in the subacute phase. 20 However, they may still play a role in stimulating adherence to prescribed PA.…”
Section: Pa Sensormentioning
confidence: 77%